A Critical Analysis of the Compulsory Science Education Policy at the Secondary Level of Education in Uganda - Milliam, Kiconco; Dominic, Karyarugokwo (Advances in Social Sciences Research Journal, 2022)
Uganda is one of the African countries that have been focusing on the science-led strategy to promote growth and development. One of the strategies is the science promotion policy, which started in 2005 and among other things made learning and enrolling on science subjects (mathematics, chemistry, physics and biology) compulsory at the ordinary level of secondary school education. This paper has, therefore, used a secondary review methodology to critically analyse the science policy at the secondary school levels (ordinary and advanced). The paper begins with an introduction that discusses the history of curriculum reform at the secondary school level globally and in Africa with emphasis on Uganda. It also discusses Uganda’s science policy implementation strategies, which included the government’s effort in providing resources such as laboratory equipment and science textbooks to government-aided schools. There is, then, a section that discusses the challenges that have hindered the successful implementation of science policy. This section shows that much as the government of Uganda has tried to facilitate science policy, the latest being the enhancement of salary for scientists, including science teachers by 300%, factors such as unresponsive curriculum content, shortage of qualified science teachers and inadequate laboratory equipment remain challenges to the, otherwise, good policy. The paper concludes by stating that improvement in science performance requires a multi-dimensional approach and, therefore, the recent salary enhancement that only catered for science teachers may not, necessarily, achieve much as far as improvement in the performance of students in science subjects is concerned